The association between victim-offender relationship and the age of children and adolescents who suffer sexual violence: a cross-sectional study - Evaldo Lima da Costa; Anibal Faúndes; Rui Nunes (Elsevier, 2022)
Objectives: Sexual violence is a problem that affects children and adolescents regardless of social class, age, origin, religion, education level, marital status, race, or sexual orientation. This study aimed to analyze the associations between victim-offender relationships and the victim's age in cases of sexual violence involving female victims. Methods: This cross-sectional, retrospective observational study used data from the Brazilian Ministry of Health's Department of Public Health Surveillance in Brasília regarding the reportable crime of rape as informed by female victims in the Federal District between January 1, 2012, and December 31, 2018. The age of the victim was classified as <15 years or 15-19 years. The offenders were classified into eight different categories according to their relationship with the victim: father, stepfather, brother, husband, boyfriend, friend, stranger, and others. The association between the victim-offender relationship and the victim's age was assessed. Results: Overall, there were 4,617 reported cases of sexual violence, with 78.3% of these (n = 3614) corresponding to children under 15 and 21.7% to adolescents 15-19 years old (n = 1003). Close relatives, including brothers, and friends were the main perpetrators in cases of girls < 15 years old. Strangers and friends were the principal perpetrators in the group of girls 15-19 years old. Conclusions: Children under 15 are the group most affected by sexual violence. Strategies must be developed to prevent the sexual abuse of children and adolescents and to facilitate the rehabilitation of victimized children.